115k views
4 votes
Multiply.

(x - 6)(3x^2 + 10x - 1)

A) 3x^3+ 10x^2 - x
B) 3x^3 - 8x^2 - 61x + 6
C) 3x^3 + 10x^2 - 60x + 6
D) 3x^3 - 18x^2 + 10x^2 + 6

1 Answer

5 votes
We could use distribution property to determine the result
(x - 6)(3x² + 10x - 1)
= (x)(3x²) + (x)(10x) + (x)(-1) - 6(3x²) - 6(10x) - 6(-1)

Then simplify the algebraic form, classify the one have same variable
= 3x³ + 10x² - x - 18x² - 60x + 6
= 3x³ + 10x² - 18x² - x - 60x + 6
= 3x³ - 8x² - 61x + 6

The answer is b
User Gopal Gopi
by
6.2k points